(3GdhUdI aj eSCdI GdbjdI hGdMceI hGdSQs - (3YHO GdHGSW Hf Ndjd GdMfajs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdcYHI GdHjJ GdMQGe CeG HYO ajbhd GdYHO GdabjQ YHO GdHGSW GdMfai gPg QSGdI CfjbI LeYJgG ai CeQ bHdI GdESdGe heG jJYdb HgG ef GdcdGe SejJgG GdhUdI ai eSFdI GdbHdI s
(3BNQgG (B:s
(3deG HjfGg ef GdeYGfi ai Pdc XgQ dg bHdI cd Ebdje ef GdCbGdje hcd HdOI HPdc GdEbdje hGdSdGe gPG BNQ GdcdGe Ydi eSFdI bHdI GdESdGe s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeQJH GdCHLOi s
Keywords: (3GdJUha hGdBOGH GdTQYjIs